Intermediate band solar cell materials through the doping of group-VA elements (N, P, As and Sb) in Cu2ZnSiSe4. Issue 48 (9th September 2019) - Jibran, Muhammad; Sun, Xia; Wang, Bing; Yamauchi, Yasushi; Ding, Zejun
Abstract : The doping of group-VA elements in Cu2 ZnSiSe4 induces an intermediate band and enhances the absorption coefficient with two additional peaks. Abstract : The electronic structure and optical properties of group-VA (N, P, As, and Sb)-doped Cu2 ZnSiSe4 alloys have been studied using a hybrid functional through density functional theory calculations. The minor lattice distortion and small formation energy indicate that synthesis of these alloys is highly possible in experiment. For each doped alloy, an isolated and partially filled intermediate band (IB) appears in its band structure. The doping-induced IB is mainly contributed by the s states of the doped group-VA atom and the p states of four neighboring Se atoms, and slightly by the d states of eight Cu atoms. The existence of an IB obviously enhances the absorption coefficient with two additional absorption peaks in the visible light range. For P, As and Sb-doped Cu2 ZnSiSe4 alloys, not only the bandgap between the valence band maximum and the conduction band minimum but also the sub bandgap between the valence band maximum and the IB are very close to the optimal values for visible light absorption. Therefore, these alloys are recommended as good candidates for IB solar cell materials.